ANALYSIS OF PRESUPPOSITION USED IN ENCANTO MOVIE SCRIPT - Pramesti, Dhea Arning; Dieni, Novita Al Ihyak (LINGUAMEDIA Journal, 2023)
Presupposition is one of the topics in pragmatic studies. In this thesis, the writers focuse more on the discussion of presuppositions in pragmatic studies, where presuppositions are everything that is in one's mind about everything that exists in this world. Presuppositions are needed to understand the meaning of a conversation between the speaker and the listener so that there is no misunderstanding in communication. In this research the writers use a descriptive research method, because all data comes from film script. Presuppositions in Encanto movie taken from the dialogues of the characters in the movie and analyzed based on the theories by Yule (1996) and classifying them into various types of presuppositions. The result of this study shows that there are many variation of presupposition contained in this move script. There are six presuppositions, specifically 5 existential, 14 factive, 1 non-factive, 3 lexical, 23 structural, and 5 counterfactual. Data analysis shows that there are several types of presuppositions contained in this movie. From this research, the writers hope that this thesis can be useful as an additional knowledge for future researchers who discuss pragmatic studies, especially presuppositions.